Mobile learning for the integration of groups that risk being marginalized - Maria Ranieri; Giovanni Bonaiuti; Antonio Fini; Pierfranco Ravotto (Je-LKS: Journal of E-Learning and Knowledge Society, 2009)
Social inclusion and cohesion are two of the objectives that the European Union has very often proclaimed in its documents, in the past ten years. At the same time, community policies have emphasized the role that ICTs can play to encourage and support participation and integration opportunities of disadvantaged citizens. Within this context, the ENSEMBLE project, presented here, aims at developing a strategy of use of ICTs to promote socio-cultural integration of immigrant citizens by using technologies such as MP3 players and mobile phones, and by experimenting instructional methods and communication models suitable for the adopted instruments. The present paper focuses particularly on the educational communication design of MMS messages.